FAKTOR FAKTOR YANG MEMPENGARUHI KINERJA PEMERIKSA PAJAK - Merrisa Susanti; Vince Ratnawati; Nasrizal Nasrizal (PEKBIS, 2020)
Performance is the result of work in quality and quantity achieved by an employee incarrying out his duties in accordance with the responsibilities given to him. Improvingperformance Tax auditors are very important in increasing state revenues throughthe taxation sector. This study has several objectives, first to analyze the effect ofprofessionalism on the performance of tax auditors, second, analyze the influence ofself efficacy on the performance of tax auditors, third, analyze the effect of locus ofcontrol on tax audit performance, fourth, analyze the influence of organizationalcommitment on tax audit, to analyze the effect of professionalism, self efficacy, locusof control, organizational commitment on the performance of tax auditors after beingmoderated by role conflict. Role conflicts are expected to have an influence on theperformance of tax auditors. Data obtained from the answers to questionnaires weredistributed to 125 tax auditors in the Riau Regional Directorate General's Tax Office.By using Smart PLS Version 3.2.8, the results show that organizational commitmentdoes not affect the performance of tax auditors and professionalism, self efficacyand locus of control positively significantly affect the performance of tax auditors.While that role conflict does not moderate the relationship between professionalism,self efficacy, locus of control and organizational commitment on the performance oftax auditors.